First, remember that (x+a)2 = x2 +2ax + a2 so the first step in completing the square is to realize that the binomial you want is (x + (b/2)) which, when squared gives x2 + bx + b2/4.
Therefore you need to subtract the b2/4 from the expression later on.
In the current example you will want (x + 6)2
and you will then need to solve:
(x + 6)2 - 36 -28 = 0 => (x + 6)2 = 64
Remember when you completed the square you added 36 which now must be subtracted.
then (x + 6) = ±8
The solutions are x = 2 and x = -14
Just for practice you might want to develop the quadratic formula which comes about by completing the square of the generalized quadratic: Ax2 + Bx + C = 0.